The association of serotype and pulsed-field gel electrophoresis genotype in isolates of Streptococcus pneumoniae isolated in Israel. (May 2015) - Bar-Meir, M.; Naaman, G.; Assous, M.; Korenman, Z.; Valinsky, L.; Picard, E.
Highlights: A close correlation between pneumococcal serotype and pulsed-field gel electrophoresis (PFGE) genotype was demonstrated, although the genetic diversity varied by serotype. Serotypes 6A and 12F were found to be mostly clonal, while serotypes 18C and 19A had high genetic diversity and were represented by multiple clones. A correlation was found between PFGE clone and penicillin minimum inhibitory concentration (MIC), with clones C and D presenting higher penicillin MICs. These data suggest that serotyping alone would not be sufficient for surveillance in the era of the conjugated vaccines, and clonal distribution should be monitored to detect replacement disease. Summary: The relationship between Streptococcus pneumoniae isolates causing invasive infections in children admitted to a single center in central Israel was examined by pulsed-field gel electrophoresis (PFGE) and serotyping. Although there was a close correlation between serotype and PFGE clone, the genetic diversity varied by serotype, with some genotypes comprising multiple serotypes. Additionally, clones C and D were associated with higher penicillin minimum inhibitory concentrations. Serotyping alone may be insufficient for epidemiological mapping of pneumococcal isolates in the era of pneumococcal conjugate polysaccharide vaccines.